(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Customer loyalty indicates the alignment between a person’s expectations and the rewards provided by the service. Factors that influence customer loyalty include service quality and price. This study aims to determine the effect of service quality and price on customer loyalty. The research method used is quantitative, conducted on consumers of Villa Metteya Ubud. The sample consisted of 70 respondents. The data analysis techniques employed include validity and reliability tests, classical assumption tests, multiple linear regression, coefficient of determination, t-test, and F-test. The results show that service quality has a positive and significant effect on customer loyalty, as evidenced by a t-value of 4.749 and a significance value of 0.000. Price also has a positive and significant effect on customer loyalty, with a t-value of 2.112 and a significance value of 0.040. Simultaneously, service quality and price have a positive and significant effect on customer loyalty, as evidenced by an F-value of 47.474 and a significance value of 0.000. The study suggests that Villa Metteya Ubud Bali should supervise employees when providing services to ensure quick and timely service, evaluate pricing policies to match service quality and facilities, and consistently provide quality service and appropriate pricing so that customers are not attracted to switch to other villas.